INFLUENCE FACTORS ON GROWTH AGROECOLOGICAL SPRINGDURUMWHEAT DEPENDING FERTILIZERS ANDBIOLOGICS - Жемела, Г. П.; Шевніков, Д. М. (Scientific Progress & Innovations, 2013)
The use of fertilizers and inoculation of wheat seeds solid spring biological products positively affected to the growth and development of plants. Effects of fertilizer on plant height was significantly more than biologics, but their complex influence was more effective in increasing the growth processes in solid spring wheat plants, in this case, apparent negative effect unfavorable growing season. Without the use of fertilizer plant height was 63.6 cm. Usingpolimiksobakterynu increased to 67.2cm, diazofitu - to 68.6 cm.